2016
DOI: 10.1007/s13280-016-0776-7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of recognition of genetic biodiversity: International policy and its implementation in Baltic Sea marine protected areas

Abstract: Genetic diversity is needed for species’ adaptation to changing selective pressures and is particularly important in regions with rapid environmental change such as the Baltic Sea. Conservation measures should consider maintaining large gene pools to maximize species’ adaptive potential for long-term survival. In this study, we explored concerns regarding genetic variation in international and national policies that governs biodiversity and evaluated if and how such policy is put into practice in management pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
(41 reference statements)
0
19
0
3
Order By: Relevance
“…This is not the case for the MPAs studied here. Not only are Baltic Sea MPAs not constructed to protect genetic variation per se (Laikre et al, ), they also rarely focus specifically on marine organisms, although their general, broad aim includes conserving biodiversity at all levels. Second, MPAs should generally fulfill several of the following key features: no take allowed (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not the case for the MPAs studied here. Not only are Baltic Sea MPAs not constructed to protect genetic variation per se (Laikre et al, ), they also rarely focus specifically on marine organisms, although their general, broad aim includes conserving biodiversity at all levels. Second, MPAs should generally fulfill several of the following key features: no take allowed (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although both international and national policies that govern Baltic Sea biodiversity identify genetic diversity as an essential component for conservation, and MPAs as a means for conserving such diversity, management plans for MPAs in the Baltic Sea are largely devoid of goals and strategies for genetic biodiversity (Laikre et al, ). Sandström et al () explored why this is the case by interviewing regional managers in the area and found that there are several possible explanations including lack of knowledge of genetic variation and how it can be used in management.…”
Section: Introductionmentioning
confidence: 99%
“…Although goals for conserving genetic diversity were clearly stated in international and national documents, they were rarely mentioned in regional documents (Laikre et al. ) (Fig. , stage 1).…”
Section: Gap Between Knowledge and Mpa Managementmentioning
confidence: 99%
“…National authorities can make a big contribution by stipulating in their instructions to regional authorities the necessity to work with genetic biodiversity and by reviewing and updating guidelines and manuals on how to form new MPAs and on what to consider when developing conservation goals and updating management plans. There is an opportunity to learn from other policy areas; genetic concerns are more prominent in terrestrial policy than in marine policy (Laikre et al ; Sandström et al. ).…”
Section: Pieces Needed To Bridge the Gapmentioning
confidence: 99%
See 1 more Smart Citation